Customer-to-customer value co-creation in different service settings. Issue 1 (13th January 2020) - Pandey, Sneha; Kumar, Divesh
Abstract : Purpose: This study aims to identify and classify the types of value stemming from cooperative creation of experience among customers present in various social and interaction-rich service settings, thus leading to customer–customer value co-creation. Design/methodology/approach: This exploratory qualitative study uses phenomenological approach and involves ten semi-structured in-depth interviews conducted in different interaction-rich service settings. The interviews were analysed using soft laddering interview technique to uncover various customer-to-customer (C2C) co-created values. Findings: Based upon the literature available and the interviews conducted, the types of value classified in this study are hedonic value (further classified as relational/social/interactional value, emotional value, epistemic/novelty/learning/information-seeking, personal value and symbolic/expressive value), atmospheric value and economic/utilitarian value (efficiency and quality). Research limitations/implications: One of the major limitations would be the small number of interviews conducted in a few service setups, which makes it difficult to generalise the results. Also, customer–customer interactions, leading to value co-creation online, were not considered. Practical implications: By facilitating C2C value co-creation, service firms would be able to obtain increased contributory support among customers and also facilitate its customers in providing superior customer experience indirectly to others present, which is considered to be the ultimate goal of a firm. Originality/value: This would be among the first studies to classify the types of value taking place when customers interact among themselves and to provide concrete suggestions for the managers fostering C2C value co-creation during a service.